ANALYSIS OF TEACHING ENGLISH DURING E-LEARNING CLASSES AT SMP NEGERI 6 PALU - Zainab; Rofiqoh, Rofiqoh; Dewi, Anjar Kusuma (Tadulako University, 2023)
This research aims to find out the teaching English process during e-learning classes at SMP Negeri 6 Palu. This research was conducted through a descriptive qualitative research design in which the results are transcribed and described. The subjects of this research were three English teachers at SMP Negeri 6 Palu. This research used interviews to collect the data. Based on the research findings, the teaching English process during e-learning classes was first the teacher preparing before e-learning classes, the teacher preparing media such as modules, laptops, attendance lists, materials to be taught and applications for online teaching such as Zoom, Google Meet and Whatsaap. Second, the teacher finds a way to make students active during e-learning classes. The teacher provides activities that can make students active such as giving projects video, asking students to retell stories, and doing questions and answers. Third, in teaching English during e-learning classes, the teachers used videos, pictures, songs, and games to convey the material depending on what material will be taught by the teachers. Fourth, problem faced by the teachers during e-learning classes, some of the teacher's problems when teaching English online, only a few students take a zoom class, and some students do not have communication tools such as cellphones or laptops. Thus, as much as possible, the teacher provides a solution to the problems.